Políticas curriculares e saberes docentes: contribuições para reorganização da matriz curricular da educação física nos anos iniciais da educação do campo - Marafiga, Taís Cecchin (2024)
This Professional Master's degree in Public Policies and Educational Management research comes from the Postgraduate Program in Public Policies and Educational Management, at the Federal University of Santa Maria (UFSM/RS), addresses the theme of school physical education and the rural education curriculum of the initial years of Elementary School. Its general objective is to investigate curricular policies and teaching knowledge for organizing the curricular matrix in physical education in the initial years of elementary school in the State Network. For specific objectives, it prioritizes: researching scientific productions with the theme of school physical education curriculum and public educational policies in rural education; analyzing curricular policies for the first and second year of the initial years of elementary school linked to the Physical Education component; Identifying the main characteristics of the physical education curriculum in rural education. The theoretical framework is organized based on authors Morosini (2015), Azevedo (2003), Saviani (2005), Sacristán (2002), Lopes (1999), Caldart (2002), Darido and Rangel (2005), Bracht (2003) and legislation in the context of basic education. It is based on research with a qualitative approach supported by Ludke and André (1986), of the case study type, which was carried out in a rural school in the state network in the Municipality of Santa Maria/RS, with pedagogues and physical education teachers from the initial years courses (1st and 2nd years) and with a pedagogical coordinator. To this end, questionnaires will be used, based on Gil (2008) and content analysis based on Minayo (2010) will be used to analyze the data. The research results point to a curriculum that must have the identity of the school's reality, supported by educational policies. To achieve this, the teacher must know the school community's context and be sensitive to adapt their curriculum according to the student's experiences. This research aims to contribute to the specificities of the physical education curriculum in the context of rural schools.